A Community-based Case Study of Coffee Farming in Thailand - Arayawut , Saramon (International Journal of Multidisciplinary in Management and Tourism, 2020)
Coffee farming is very important to Chiang Rai, Thailand, and most of the coffee crops are produced in the highlands of ethnicity-crowded communities. Nevertheless, a rich case understanding of how the coffee farming has been practicing is lacking. Relying on in-depth interviews and field observations, this study presents how a specialty coffee farmer integrates sustainable farming practices and market orientations in a management framework that resembles balanced scorecard (BSC) and strategy mapping concepts. The case illuminated is award-winner which testifies to the central role of sustainability principle and motivators to stimulate learning and growth of the farmer, and in turn, contributes to continuing improvement of farming, coffee-making and marketing processes, to contribute to the sustainability aspects of performances. The semi-structured interview protocols, which provide the guidelines to guide the interviewing process, are facilitated using the CATWOE-guided root definition concept of the soft-systems methodology (SSM) to ensure triangulated coverage of important respondents and the coverage scopes for systemic insights.